The crisis years 1980 and the film exhibition - Simis, Anita [UNESP] (Univ Federal Sergipe, 2016)
In this research, we try to review the explanations of a troubled period for Brazilian cinema, specifically one that covers the years 1980 and mid 1990. As we all know it will be shown that there was a sharp drop in film production, but it was also the time in which data about the viewing public fluctuated dramatically and that the movie theaters, after coming into decay, resurfaced, now organized into a new exhibition system - the Multiplex. So we will summarize some key aspects of this period of crisis, trying to establish significant milestones of rupture or movie crisis, arguing that it is from a look at the exhibitor sector that we can find the keys to understand the dismantling of a film and the construction of another.
Keywords: Crisis in brazilian cinema; Film exhibition; Embrafilme